La suegra «mata» a la nuera: dos ejemplos del motivo en las baladas tradicionales griegas y en el romancero - Ioannis Kioridis (Atalaya)
The present study addresses the issue of the relationship between «the wicked mother-in-law» and her daughter-in-law, based on two examples, from Greek folk songs and Spanish romancero respectively. In these cases, the mother-in-law either instigates the death of, or kills her son’s wife herself. The author initially presents a literary review of the pattern of «the wicked mother-in-law» in both traditions, and also refers to the comparative studies that have been devoted to the two traditions so far. He then analyses the two songs by referring them to the broader socio-cultural framework in which they were created, thus interpreting the behaviour of the individuals involved. He then finds analogies and differences and also points out the excellence of both folk poets in the handling of the issue. The author concludes that, in his opinion, the aim was to defend inbreeding and the nuclear family against exogamy –which was common at the time- and against the extended family. The study ends with an annex that includes the respective songs.